PERSEPSI MASYARAKAT TENTANG PERKAWINAN USIA MUDA DI KELURAHAN KOTO PANJANG IKUA KOTO KECAMATAN KOTO TANGAH KOTA PADANG - -, Yulasmiati - (Pendidikan Geografi, 2014)
Based on data from the Religious Affairs Office (KUA) in the village of Koto Koto Panjang subdistrict Ikua Tangah Koto Padang, from 2011 through 2013 that nearly 50% Ikua Koto Koto Panjang Society, three years later, many carry out marriage a young age. Early marriage occurs between the ages of 17-19 years. Based on the existing reality in the Village District of Koto Koto Koto Panjang Ikua Tangah Padang, worth exploring further. The purpose of this research was to determine the perception (sight) of young people about the marriage. This study used qualitative methods. The informants are ninik mamak, community, parents whose children married young and young married people, using purposive method. Data was collected by means of direct observation and interviews. The researcher also did a study of the documents supporting data seta evidence used by the author to support the data collection. From the results of research conducted in the village of Koto Koto Panjang Ikua concluded the causes of early marriage are caused by self-will, dropouts, and promiscuity. The impact of child marriage is for the husband and wife often quarrel, threatened to fail and have an impact on divorce. When it comes to young children aged couples are less skilled, and still expect help from parents. In the economic problems young married couple who still expect help parents, so parents feel burdened.